2017
DOI: 10.5812/mcardia.62857
|View full text |Cite
|
Sign up to set email alerts
|

Association of Perioperative Serum Sodium Level Fluctuation and Postoperative Complications in Coronary Artery Bypass Graft Surgery

Abstract: Background: Electrolyte abnormalities are common in coronary artery bypass graft surgery (CABG) using cardiopulmonary bypass (CPB). Changes in serum sodium (Na) concentration more than 15 meq/L in perioperative period (Delta Na > 15) is considered as significant fluctuation. The aim of this study was evaluating the relationship between the significant fluctuation of serum Na level and the complications after coronary artery bypass graft surgery. Methods: In this prospective observational study 59 patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, what is neglected in some hospitals is the important role that nurses can play in reducing the anxiety among the family caregiver of patients who are in waiting rooms. Currently, the focus of nurses is on the patient, and the information and care needs of family caregivers usually are neglected during this anxious period (16). Therefore, the family caregivers inadvertently transfer anxious feelings to their relatives after surgery if they are unable to cope with these feelings (17).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…However, what is neglected in some hospitals is the important role that nurses can play in reducing the anxiety among the family caregiver of patients who are in waiting rooms. Currently, the focus of nurses is on the patient, and the information and care needs of family caregivers usually are neglected during this anxious period (16). Therefore, the family caregivers inadvertently transfer anxious feelings to their relatives after surgery if they are unable to cope with these feelings (17).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Our study suggested that both video training and intraoperative progress report for family caregivers help reduce their state anxiety in the waiting room. One of the main reasons for family caregivers' anxiety in the waiting room is their lack of knowledge and information about the surgical process (16). Accordingly, video training and intraoperative progress report can provide relevant information to the family caregivers.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%